The Impact Of Using A Task-based Writing To Promote Business Students Writing Skill - Ali Nouar (Al-Lisaniyyat, 2020)
The present research aims at determining the effects of the Task Based Approach on Business students‘ writing skills so as to suggest and recommend it or discourage its use at English for Business Purposes classrooms. The effect of the Task Based Approach has been measured in different English teaching and learning environments. However, only few studies have been carried out to test the effect of the approach in ESP settings. This research goes further than just implementing the Task Based Approach in ESP classes but it attempts to examine the effect of this teaching pedagogy on students writing skills. It is known that professionals in different business fields communicate mostly via writing, for this reason, writing skill was chosen among other language skills because of its importance to the students 3rd year LMD Banking and Insurance the sample that represents the whole population, that is, the Faculty of Business and Economics at Laghouat University and professional business areas. The current study aims at empirically examining the effect of the Task based Approach. However, random assignment of the participants in this educational experiment was impossible for the researcher, so a quasi-experimental design was utilised to provide as accurate and valid results as possible. The participants in the control and experimental groups were tested before and after the implementation of the Task Based Approach to statistically measure the effects of this teaching approach. The findings showed that the Task Based Approach improved the writing skills of the experimental group in comparison to the control group which was taught using the regular teaching methodology. Pedagogically, the Task Based Approach can be utilised to bring closer the ESP classes to the professional world as the approach is built on real-world tasks to enable the students of business to live up to the expectations and requirements of a globalised and demanding business world.